Eficacia del ibuprofeno en el control del dolor postoperatorio en la cirugía de terceros molares: revisión sistemática - Pinzón Viñan, Robert Joel (2024)
In odontology and maxillofacial surgery of third molars, known as wisdom teeth, cause regular pain, infection, and inflammation, and can turn into chronic pain. After the intervention, the post-surgery pain is mainly managed with ibuprofen, and AINE used during inflammation illness. Even with the possible gastrointestinal effect (affecting 10% of patients), ibuprofen is considered safe in moderate doses (2,400 mg/dairy). The systematic review has a goal to evaluate the efficient doses, presentations, and the beginning effects of ibuprofen during post-surgery pain of wisdom teeth. The methodology is systematic, using bases like Cochrane, Pubmed, Scielo, Redalyc, Scopus Preview, and Dialnet, checking 30 articles from 2013 until 2023, with inclusion and exclusion criteria and research strategy using terms like MeSH and DeCS. Until now, 70% of authors consider 400 mg of ibuprofen the appropriate dose, while 20% suggest 600mg and 10% recommend 800 mg. Taking into account the presentation, the 40% mention gel capsules with an action of 15 minutes, and the 30% capsules with an action started of 30 minutes. In conclusion, the 400 mg ibuprofen is effective in controlling all post-surgery pain, with possible side results that require professional revision. The choice of election and precise dosage must be individualized by a professional, considering the patient’s characteristics and the surgery done